Exploring gene signatures and regulatory networks in a rat model of sciatica: implications and validation in neuropathic pain - Xu, Mu; Wang, Zhijian; Xu, Gang; Zhu, Mengye; Zhang, Daying; Yan, Yi (Frontiers in Molecular Neuroscience, 2024)
Background Sciatica (neuropathic pain [NP]) is a common disease characterized by pain from radiation along the sciatic nerve. The aim of this study was to study the genes associated with chronic systolic injury of sciatic nerve (SCN-CCI) in rats by RNA-Seq technique, and to explore their potential as therapeutic targets. Methods Sciatic nerve rat model was obtained by ligation of sciatic nerve and divided into two groups: SCN-CCI group and Sham group. Behavioral assessments were performed to evaluate pain sensitivity, following which their spinal cord dorsal horn were resected and RNA sequencing was conducted to identify differentially expressed genes (DEGs). Bioinformatics and functional enrichment analysis was performed to identify promising DEGs and their related biological processes and pathways associated with SCN-CCI. PPI network analysis and hub gene identification were conducted. QRT-PCR, western blot, ELISA, and immunofluorescence staining were performed on rat models to validate the expression of these hub genes and investigate related proteins and inflammatory markers. Results The SCN-CCI rat model was successfully obtained, exhibiting increased pain sensitivity compared to the Sham group, as indicated by decreased mechanical allodynia thresholds, thermal latencies, and increased paw withdrawals. RNA-Seq analysis identified 117 DEGs in the SCN-CCI rat model, involved in various biological processes and pathways related to sciatica. PPI network analysis revealed hub genes, including Ly6g6e, which exhibited significant differential expression. QRT-PCR and Western blot analysis confirmed the expression patterns of these hub genes. Pain behavior assessment demonstrated reduced pain thresholds and increased paw flinching responses in the SCN-CCI group. Furthermore, the SCN-CCI group showed upregulated expression of Ly6g6e, increased protein levels of Ly6g6e, CGRP, and NGF, as well as elevated levels of IL-1β, MCP-1, and IL-6, and microglial cell activation in the spinal dorsal horn. ELISA results confirmed the increased levels of IL-1β, MCP-1, and IL-6 in the spinal dorsal horn. Conclusion These comprehensive findings provide valuable insights into the SCN-CCI rat model, DEGs associated with sciatica, hub genes (Ly6g6e as promising targets), pain behavior changes and molecular alterations.